Rearfoot angle velocities during running - a comparison between optoelectronic and gyroscopic motion analysis - Lederer, P.; Blickhan, R.; Schlarb, H. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was a verification of a gyroscopic measurement device mounted on the heel counter of a running shoe. For this purpose 15 subjects performed 10 running trials in a laboratory environment. Rearfoot angular velocities from the gyroscope were compared qualitatively and quantitatively to rearfoot angular velocities observed with a 3D motion analysis system (VICON). Based on the qualitative and quantitative analysis the results are very good in the sagittal plane, good in the frontal plane and poor in the transverse plane.